Aulas remotas de artes visuais na educação básica da rede estadual de ensino do Paraná em 2020: desafios e possibilidades - Ferreira, Fernanda Ribas Mira (2023)
The research aims to address the reflections on the teaching-learning process in visual arts classes, in the year 2020, and the possible consequences for future educational policies. As well as reflecting from the teaching perspective on the difficulties faced in the teaching-learning process, understanding the tensions experienced by teachers in remote classes in 2020 and what their perspectives are when classes return to face- to-face mode. Our goal is to encourage reflection on theoretical and practical references in the field of teaching visual arts based on experiences during the pandemic, analyze the results obtained from semi-structured interviews with the research group and, finally, propose solutions using technology in a new university extension course. As a theoretical reference, we cite Barbosa (2001) and Saviani (1996) as essential for our research. and non-explicit discourse of the subjects involved, teachers of visual arts, with a qualitative approach.